The effect of pulmonary rehabilitation on mortality, balance, and risk of fall in stable patients with chronic obstructive pulmonary disease: a systematic review - Hakamy, Ali; Bolton, Charlotte E.; McKeever, Tricia M. (Sage, 2017)
Objectives: To evaluate the impact of pulmonary rehabilitation on survival and fall (including balance) in patients with chronic obstructive pulmonary disease (COPD) at stability.